The Effect of Earning Per Share (EPS) and Price Earning Ratio (PER) on Stock Prices Listed in the LQ45 Index for the 2020-2022 Period - Sugianto, Iwan; Fitriani; Ramadhan, Gunar (Jurnal Multidisiplin Madani, 2025)
This study aims to determine the effect of Earning Per Share and Price Earning Ratio on Stock Prices in companies listed on LQ45 for the 2020-2022 Period. The research method used is quantitative descriptive. The sampling method in this study uses the purposive sampling method. The sample in this study is 8 companies registered in LQ45 in the primary and non-primary consumer goods sectors. The data analysis technique used is multiple linear regression analysis with the help of IBM Statistic SPSS V. 27I software. The results of the study showed that based on the results of the T Earning Per Share Test and Price Earning Ratio, there was no significant effect on stock prices. Based on the results of the F Test, it shows that Earning Per Share and Price Earning Ratio simultaneously have a significant effect on stock prices.